Circular dichroism analysis of mononucleosome DNA conformation. - Cowman, M K (1978)
Mononucleosomes were isolated from micrococcal nuclease digests of chicken erythrocyte nuclei. The circular dichroism properties of mononucleosome preparations, differing in average DNA length and in H1 and H5 content, demonstrate that the spectrum of chromatin is due only to the complete structure of its repeating subunits. The nucleoprotein spectra are all altered relative to protein-free DNA by the emergence of a single negative band at 275 nm, similar to the band observed for psi DNA. The intensity of the psi-type band depends on the proportion of DNA condensed in a specific manner. The psi-type band is proposed to be due to the compact DNA tertiary structure; i.e., the manner in which the DNA is wound around the histone core allowing interactions between adjacent turns of the superhelix. This interpretation attributes changes and variability in nucleoprotein circular dichroism spectra under different experimental conditions to alterations in DNA tertiary structure rather than secondary structure.